Situating risk in young people's social and moral relationships: Young Lives research in Peru - Crivello, G; Boyden, J (Young Lives, 2011)
This paper examines how poverty is involved in a multitude of risks in children’s lives using data gathered from children in Peru between 2002 and 2006. Three main arguments emerge. The first is that risk is not simply a feature of ‘extraordinary’ childhood circumstances. Rather, it is part of everyday life for many children. For example, urban families in the sample experienced slightly more ‘interpersonal’ shocks, with crime and family problems relatively more prevalent in cities than rural areas. In contrast, rural families experienced more ‘structural adversities’ in the form of economic and environmental disasters. This suggests that the location where children grow up is a strong factor in shaping their exposure to certain types of risk. The second argument concerns the social and moral dimensions of risk and how these shape children’s responses to difficult events and circumstances. The study shows that children’s moral and social learning is regarded as key to their integration within family and community in rural Peru, as well as to their transitions to adulthood. Adults in rural communities are not able to shield the young from risks associated with poverty. Instead, they are often of the view that boys and girls can grow morally and socially and acquire crucial life skills by helping alleviate household hardship. It is clear that working to prevent and/or overcome risk is an ongoing process. The third argument makes the case that in situations where there is strong interdependence between family generations children often make significant contributions to the household’s risk management. They are actively a part of helping to reduce risks.